2016
DOI: 10.1016/j.diagmicrobio.2016.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Rifabutin and rifampin resistance levels and associated rpoB mutations in clinical isolates of Mycobacterium tuberculosis complex

Abstract: Cross-resistance in rifamycins has been observed in rifampin (RIF)-resistant Mycobacterium tuberculosis complex isolates; some rpoB mutations do not confer broad in vitro rifamycin resistance. We examined 164 isolates, of which 102 were RIF-resistant, for differential resistance between RIF and rifabutin (RFB). A total of 42 unique single mutations or combinations of mutations were detected. The number of unique mutations identified exceeded that reported in any previous study. RFB and RIF MICs up to 8 µg/ml b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
46
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 36 publications
7
46
0
Order By: Relevance
“…Some of these drawbacks could be overcome by designing the assay to specifically address the detection of synonymous mutations as recently done for the Xpert Ultra; however, this strategy requires a priori knowledge of all the possible silent mutations in the targeted region. Fourth, clear understanding of the relationship between genotype and phenotype and clinical outcome is not always available, and several factors contribute in complicating the clinical interpretation of genetic polymorphisms …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these drawbacks could be overcome by designing the assay to specifically address the detection of synonymous mutations as recently done for the Xpert Ultra; however, this strategy requires a priori knowledge of all the possible silent mutations in the targeted region. Fourth, clear understanding of the relationship between genotype and phenotype and clinical outcome is not always available, and several factors contribute in complicating the clinical interpretation of genetic polymorphisms …”
Section: Discussionmentioning
confidence: 99%
“…Fourth, clear understanding of the relationship between genotype and phenotype and clinical outcome is not always available, and several factors contribute in complicating the clinical interpretation of genetic polymorphisms. 19,78,79,[182][183][184][185][186][187][188][189] Beside determination of drug resistance patterns, the era of personalized medicine advocates for improved interpretation of genotype for clinical management. Increasing evidence supports that different groups of bacteria (lineages) have different features in terms of host-pathogen interactions and/or transmission (reviewed in Ref.…”
Section: Discussionmentioning
confidence: 99%
“…Although high-level cross-resistance between the two rifamycins is reported, some studies have shown RFB susceptibility in RIF-resistant strains of M. tuberculosis in association with specific rpoB mutations (Cavusoglu et al, 2004; Yoshida et al, 2010; Jamieson et al, 2014; ElMaraachli et al, 2015). Thus, it has been argued that knowing the type of rpoB mutation may have clinical implications for guiding rifamycin-based therapeutic regimens (Sirgel et al, 2013; Berrada et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…At times, variants with lower MICs are preferentially selected at lower rifampicin concentrations in the laboratory and clinic (van Ingen et al, 2011;Lindsey et al, 2013;Berrada et al, 2016). Mutations with high rifampicin resistance confer growth defect because they occur close to the catalytic site of RNA polymerase (Campbell et al, 2001) and consequently are detrimental to the cell (Brandis & Hughes, 2018).…”
Section: Fitness Estimates Help Understand the Biochemical Basis For mentioning
confidence: 99%